2006
DOI: 10.3892/or.15.3.595
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of CCAAT/enhancer binding protein β correlates with prognosis in glioma patients

Abstract: Abstract. C/EBP ß (CCAAT/enhancer binding protein ß) is a transcriptional factor that belongs to the basic region-leucine zipper class DNA-binding proteins and plays a role in cell differentiation and inflammatory reactions. Although high tissue levels of inflammatory cytokines, such as interleukin (IL)-6, IL-8 and transforming growth factor-ß, have been observed in glioma patients, the mechanisms underlying this phenomenon remain to be elucidated. C/EBP ß induces a variety of cytokines and thus may play a rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
3
21
0
Order By: Relevance
“…Other studies show that C/EBPβ and STAT3 can individually regulate glioma biology. For example, downregulation of C/EBPβ in glioma cells inhibited proliferation, invasion and tumorigenicity in mice (Aguilar-Morante, Cortes-Canteli, Sanz-Sancristobal, Santos, & Perez-Castillo, 2011; Homma et al, 2006), consistent with findings demonstrating that increased mRNA and protein levels of C/EBPβ are associated with a worse prognosis (Homma et al, 2006). Similarly, STAT3 is known to promote tumor growth in glioma.…”
Section: Proneural-to-mesenchymal Transition (Pmt) In Gliomasupporting
confidence: 80%
“…Other studies show that C/EBPβ and STAT3 can individually regulate glioma biology. For example, downregulation of C/EBPβ in glioma cells inhibited proliferation, invasion and tumorigenicity in mice (Aguilar-Morante, Cortes-Canteli, Sanz-Sancristobal, Santos, & Perez-Castillo, 2011; Homma et al, 2006), consistent with findings demonstrating that increased mRNA and protein levels of C/EBPβ are associated with a worse prognosis (Homma et al, 2006). Similarly, STAT3 is known to promote tumor growth in glioma.…”
Section: Proneural-to-mesenchymal Transition (Pmt) In Gliomasupporting
confidence: 80%
“…Emerging evidence has shown that C/EBPb exists in three isoforms: LAP1, LAP2 and LIP, and that dysregulation of C/EBPb is markedly correlated with malignancy of several tumors, including glioma, Wilms tumors, renal cell carcinoma and ovarian tumor (Homma et al, 2006;Li et al, 2005;Oya et al, 2003;Sundfeldt et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…CCAAT/enhancer binding protein β (C/EBPβ) plays an important role in GBM cell growth, migration and invasion through EMT regulation, reduction of its expression inhibits the growth and invasion of glioblastoma cells343738. In epithelial to mesenchymal transition, E-cadherin is a marker of epithelial phenotype, while, N-cadherin and vimentin are the markers for mesenchymal phenotype39; Twist, slug and snail are the master regulators of the epithelial-mesenchymal transition4041, they worked coordinately in regulation of GBM cell migration, invasion and metastasis through induction of EMT.…”
Section: Discussionmentioning
confidence: 99%